Genome-wide scan demonstrates significant linkage for male sexual orientation. Issue 7 (17th November 2014) - Sanders, A. R.; Martin, E. R.; Beecham, G. W.; Guo, S.; Dawood, K.; Rieger, G.; Badner, J. A.; Gershon, E. S.; Krishnappa, R. S.; Kolundzija, A. B.; Duan, J.; Gejman, P. V.; et al.
Abstract : Background: Findings from family and twin studies support a genetic contribution to the development of sexual orientation in men. However, previous studies have yielded conflicting evidence for linkage to chromosome Xq28. Method: We conducted a genome-wide linkage scan on 409 independent pairs of homosexual brothers (908 analyzed individuals in 384 families), by far the largest study of its kind to date. Results: We identified two regions of linkage: the pericentromeric region on chromosome 8 (maximum two-point LOD = 4.08, maximum multipoint LOD = 2.59), which overlaps with the second strongest region from a previous separate linkage scan of 155 brother pairs; and Xq28 (maximum two-point LOD = 2.99, maximum multipoint LOD = 2.76), which was also implicated in prior research. Conclusions: Results, especially in the context of past studies, support the existence of genes on pericentromeric chromosome 8 and chromosome Xq28 influencing development of male sexual orientation.